Observations of Cepheids in Pi of the Sky experiment - Siudek, M.; Barnacka, A.; Kaminski, B.; Malek, K.; Mankiewicz, L.; Sokolowski, Marcin; Zarnecki, F. (2011)
In this paper we present analysis of Cepheids using data obtained by the Pi of the Sky detector located in Las Campanas Observatory in season 2006-2009. We have identified nearly 150 Cepheids classified as classical, overtone or population II Cepheids. The calculation of Fourier parameters of Cepheid light curves is described. In order to facilitate Fourier analysis we developed a new program capable to determine a variability period and calculate Fourier coefficients. Additional program allow for automatic classification of the variability type of Cepheid basing on neural network. Results of automatic classification of Cepheids based on a neural network are shown. © 2011 SPIE.